Adelma Vay - spregledana zdravilka iz Slovenskih Konjic - Židov, Nena (Etnolog. Nova vrsta (Ljubljana), 2015)
Adelma von Vay (1840-1925) was a baroness, who lived in Slovenske Konjice from 1867 onwards. She was considered a highly successful spiritualist and medium in her time and was held in high esteem in occult circles in Europe and America. The article presents her mainly as a healer, who used homeopathy and magnetism to treat the local peasant population as well as patients from around Europe and America.
Keywords: Vay, Adelma von, 1840-1925; biografije; zdravilke; zdravilstvo; homeopatija; magnetizem; spiritizem; Slovenske Konjice; zgodovinski pregledi